ALDHHIGH Population Is Regulated by the AKT/β-Catenin Pathway in a Cervical Cancer Model - Sarabia-Sánchez, Miguel Ángel; Alvarado-Ortiz, Eduardo; Toledo-Guzman, Mariel Esperanza; García-Carrancá, Alejandro; Ortiz-Sánchez, Elizabeth (Frontiers in Oncology, 2020)
ALDH is an enzyme involved in different cellular processes, including cancer. It has been shown that a cellular subpopulation with high ALDH activity (ALDHHIGH) within a tumor is related to functional capabilities such as stemness, chemoresistance and tumorigenicity. However, few studies have focused on determining the mechanisms behind ALDH activity within the cells. Previously, our group reported that ALDHHIGH cells have higher tumorigenicity in Cervical Cancer (CC) cell lines. Based on this, we were interested to know the molecular mediators of the ALDHHIGH cells, specifically β-catenin, inasmuch as β-catenin is regulated through different pathways, such as Wnt signaling, and that it acts as a transcriptional co-activator involved in cancer progression. In this work, we show that the increase in ALDHHIGH cell percentage is reverted by β-catenin knockdown. Consistently, upon GSK3-β inactivation, a negative regulator of β-catenin, we observed an increase in ALDHHIGH cells. Additionally, we observed a low percentage of cells positive for Fzd receptor, suggesting that in our model there is a low capacity to respond to Wnt ligands. The analysis of ALDHHIGH cells in a sphere formation model demonstrated the active state of AKT. In accordance with this, impairment of AKT activity not only reduced β-catenin active state, but also the percentage of ALDHHIGH cells. This corroborates that AKT acts upstream of β-catenin, thus affecting the percentage of ALDHHIGH cells. In conclusion, our results show that ALDHHIGH cells are dependent on β-catenin, in spite of the Wnt pathway seems to be dispensable, while AKT emerges as central player supporting a mechanism in this important axis that is not yet well known but its analysis improves our understanding of ALDH activity on CC.